Experimental infection of domestic geese (Anser anser var. domesticus) with H5N8 Gs/GD and H7N1 highly pathogenic avian influenza viruses. Issue 6 (1st November 2020) - Sánchez-González, R.; Ramis, A.; Nofrarías, M.; Wali, N.; Valle, R.; Pérez, M.; Perlas, A.; Majó, N.
ABSTRACT: Prior to the emergence of the Asian-origin H5 Goose/Guangdong/1/96 (Gs/GD) lineage, highly pathogenic avian influenza viruses (HPAIV) had rarely caused high mortalities in domestic geese. In 2016/2017 European epidemics, H5N8 Gs/GD clade 2.3.4.4 Group B produced an unprecedented number of outbreaks in waterfowl holdings. In this study, the pathogenesis of H5N8 HPAIV in comparison with H7N1 HPAIV, and the role of domestic geese in the epidemiology of these viruses, were evaluated. Local and commercial geese ( Anser anser var. domesticus ) were intranasally inoculated with 10 5 ELD50 of A/goose/Spain/IA17CR02699/2017 (H5N8) or A/Chicken/Italy/5093/1999 (H7N1) and monitored daily during 15 days. H5N8 was highly virulent to domestic geese, reaching 100% mortality by 10 days post-infection. Systemic microscopic necrotizing lesions associated with widespread AIV-antigen were detected by IHC techniques, the central nervous system being the most severely affected. High viral loads, measured by qRT-PCR, were present in all samples collected: oral and cloacal swabs, plasma tissues, and moderate levels in pool water. Domestic geese were also susceptible to H7N1 infection, as demonstrated by seroconversion and detection of viral RNA in tissues and plasma in some geese, but all lacked clinical signs. Viral shedding was confirmed in only some geese and was restricted to the oral route, but levels were high and still detected at the end of the study. Overall, H7N1 presents a lower lethality and shedding than H5N8 in geese; however, the viral shedding indicates that these species could play a role in the epidemiology of Gs/GD and other lineages of HPAIVs. RESEARCH HIGHLIGHTS H5N8 Gs/GD clade 2.3.4.4 Group B is highly virulent to domestic geese. The severity of H5N8 is associated with multisystemic replication. H7N1 can infect domestic geese but is avirulent to this species. Domestic geese could play a role in the epidemiology of Gs/GD HPAIVs.